Mitra Pengemudi Gojek dalam Jeratan Ekonomi Berbagi Melalui Platform - Anggalih Bayu Muh. Kamim; M. Rusmul Khandiq (Universitas Gadjah Mada, 2019)
This study will examine digital work relations that occur between driver partners with PT. Gojek Indonesia which happened because of business management based on digital platforms in the form of applications. The use of this platform has caused a change to existing work relations, especially in terms of existing contracts and wage systems. Gojek as a platform-based business is in great demand by the younger generation of workers because it's working hour's flexibility, higher wages, and bonuses offered. However, in fact, there are many workers' rights that are not fulfilled by Gojek to their driving partners. By using data collection methods in the form of documentation studies and data analysis carried out through the stages of reduction, presentation, verification, and conclusion, it was found that Gojek partners experienced vulnerabilities due to the use of a partner system that eliminated some workers' rights such as social security, overtime salaries, absence of severance pay, and partner relations patterns that were more subordinated. In addition, the welfare promised, in the end, is only an illusion because partners must experience exploitation in the form of unreasonable hours of work, incompatibility with income as promised, and business relationship gaps.